Allelic variants of IL1R1 gene associate with severe hand osteoarthritis - Harilainen Arsi; Saarela Janna; Kouhia Sanna T; Näkki Annu; Tallroth Kaj; Videman Tapio; Battié Michele C; Kaprio Jaakko; Peltonen Leena; Kujala Urho M (BMC, 2010)
Abstract Background In search for genes predisposing to osteoarthritis (OA), several genome wide scans have provided evidence for linkage on 2q. In this study we targeted a 470 kb region on 2q11.2 presenting the locus with most evidence for linkage to severe OA of distal interphalangeal joints (DIP) in our genome wide scan families. Methods We genotyped 32 single nucleotide polymorphisms (SNPs) in this 470 kb region comprising six genes belonging to the interleukin 1 superfamily and monitored for association with individual SNPs and SNP haplotypes among severe familial hand OA cases (material extended from our previous linkage study; n = 134), unrelated end-stage bilateral primary knee OA cases (n = 113), and population based controls (n = 436). Results Four SNPs in the IL1R1 gene, mapping to a 125 kb LD block, provided evidence for association with hand OA in family-based and case-control analysis, the strongest association being with SNP rs2287047 (p-value = 0.0009). Conclusions This study demonstrates an association between severe hand OA and IL1R1 gene. This gene represents a highly relevant biological candidate since it encodes protein that is a known modulator of inflammatory processes associated with joint destruction and resides within a locus providing consistent evidence for linkage to hand OA. As the observed association did not fully explain the linkage obtained in the previous study, it is plausible that also other variants in this genome region predispose to hand OA.